Analisis Faktor Ketepatan Pengembalian Berkas Rekam Medis Rawat Inap di RSKIA PKU Muhammadiyah Kotagede Yogyakarta - Vhita Shary Anggraini; Sri Suparti; Wahyu Ratri Sukmaningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
Delays in returning inpatient medical record documents may disrupt the continuity of services in the medical records unit, particularly in data processing, information retrieval, and healthcare service delivery. This study aimed to evaluate the effects of staff workload, the completeness of medical record documents, and the implementation of Standard Operating Procedures (SOPs) on the timeliness of returning inpatient medical record documents. This research employed a qualitative method with a descriptive approach. The informants consisted of five ward nurses, while observations were conducted on 100 inpatient medical record documents. The findings revealed that 62% of the medical record documents were returned late. Most informants (60%) stated that excessive workload was the primary obstacle, while 57% of the medical record documents were incomplete and 60% of the informants had not fully implemented the SOPs. These results indicate that high workload, incomplete medical record documentation, and inadequate implementation of SOPs are the main factors affecting the timely return of inpatient medical record documents. Therefore, improving compliance with SOPs, optimizing workload management, and strengthening supervision of document completeness are essential to enhance the quality and efficiency of medical record services.